Jamaica : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2000)
The paper suggests steps to improve the efficiency of the foreign exchange market in Jamaica, and to promote its development. The financial system in Jamaica has undergone significant improvements. The most pressing problem continues to be inadequate liquidity. The results of various approaches and indicators employed to assess the competitiveness of the economy is presented. The paper discusses the social protection programs and assesses the scope to strengthen them. The statistical data on the economic indices of Jamaica are also presented in the paper.